The ecosystem approach to fisheries - Bianchi, G. (Gabriella); Skjoldal, Hein Rune.; Food and Agriculture Organization of the United Nations; Bergen Conference on Implementing the Ecosystem Approach to Fisheries (2006 : Bergen, Norway) (Wallingford, UK ; Cambridge, MA : CABI ; Rome : Food and Agriculture Organization of the United Nations, 2008)
"Sustainable use of aquatic ecosystems is high on regional, national and international agendas and central to the implementation of international agreements on biological diversity, responsible fisheries and fish stock management. Since 2001, when political commitments were made to implement the ecosystem approach, countries have begun to incorporate ecosystem considerations into their fisheries management and have met with varied success." "The Ecosystem Approach to Fisheries covers both theoretical and applied aspects of sustainable management, with a particular emphasis on reviewing concepts and addressing implementation issues in the form of case studies from around the world. Personal experiences are considered from diverse backgrounds and discuss the constraints encountered, strategies identified and best practices to facilitate further implementation."--BOOK JACKET.
"Published by Food and Agriculture Organization of the United Nations."
"This book is based on ... the Conference on Implementing the Ecosystem Approach to Fisheries held in Bergen (Norway) on 26-28 September 2006"--P. xiii.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Sustainable fisheries -- Congresses; Fishery management -- Congresses; Marine ecology -- Congresses